2022
DOI: 10.3389/fneur.2022.872500
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Slowly Progressive Subtype of Lower Limb Onset ALS From Typical ALS Depends on the Time of Disease Progression and Phenotype

Abstract: BackgroundFlail leg syndrome (FLS) is a regional variant of amyotrophic lateral sclerosis (ALS) with the characteristics of slow progression and the symptoms confined to the lumbosacral region for extended periods. However, FLS may not be easily differentiated from typical ALS.ObjectiveThe objective of the study was to determine a cutoff time of disease progression that could differentiate FLS from the typical lower limb onset ALS.MethodsA cutoff point analysis was performed with maximally selected log–rank st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…According to Wijesekera et al ( 4 ) UK and Melbourne clinical studies, FLS is defined as a progressive, distal onset LMN pattern of weakness and wasting confined solely to the lower limbs for at least 12 months. Deep tendon reflexes from the lower limbs are usually diminished or absent; however, brisk lower limb DTRs or positive Babinski sign do not preclude the diagnosis of FLS, as long as hypertonia and clonus are absent ( 3 , 4 ). FLS of asymmetric onset may present with brisk DTRs from unaffected limbs ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Wijesekera et al ( 4 ) UK and Melbourne clinical studies, FLS is defined as a progressive, distal onset LMN pattern of weakness and wasting confined solely to the lower limbs for at least 12 months. Deep tendon reflexes from the lower limbs are usually diminished or absent; however, brisk lower limb DTRs or positive Babinski sign do not preclude the diagnosis of FLS, as long as hypertonia and clonus are absent ( 3 , 4 ). FLS of asymmetric onset may present with brisk DTRs from unaffected limbs ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS) is the most common motor neuron disease, which in its classic form is characterized by symptoms of simultaneous upper and lower motor neuron involvement at the onset ( 1 ). It has a mean prevalence of 5.4/100.000 in Europe ( 1 ) with flail leg syndrome (FLS, also known as pseudopolyneuritic variant) accounting for up to 5% of ALS cases ( 2 ), in which lower motor neuron signs predominate at onset, affecting the lower limbs usually as a triad of distal paresis, muscle atrophy, and hyporeflexia/areflexia ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study analyzed stool samples from ALS patients, concluding that, as in previous studies, ALS patients showed a loss of diversity in their GM. Moreover, they found that majority of patients had high intestinal inflammation (measured by the presence of metabolites such as LPS) [274]. Therefore, the use of prebiotic, probiotic, or metabolite treatments (for example, Prevotella spp., or changing butyrate metabolism) could be useful in the treatment of ALS [275].…”
Section: • Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…It affects both upper and lower motor neurons, and shows rapid progress of muscular atrophy and respiratory muscle weakness.FLS is a variant type of ALS , symptoms of which limited in lower limbs and it progresses slowly in a long time after disease's onset. [2]Here we report a case of FLS that admitted in the seventh Affiliated Hospital of Sun Yat-sen University in May 2022. We summarized its clinical characteristics in combination with published literatures.…”
mentioning
confidence: 98%